If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2x + 4) = 12 Reorder the terms: -2(4 + 2x) = 12 (4 * -2 + 2x * -2) = 12 (-8 + -4x) = 12 Solving -8 + -4x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -4x = 12 + 8 Combine like terms: -8 + 8 = 0 0 + -4x = 12 + 8 -4x = 12 + 8 Combine like terms: 12 + 8 = 20 -4x = 20 Divide each side by '-4'. x = -5 Simplifying x = -5
| y^2+y=.75 | | 19-5/3x=4 | | 12/7=36/m | | 6/z=3/5 | | 9/g=15/10 | | p=6h/-3+y | | 5u-10=-3u-10 | | p=h+5h/-3+y | | (y-3)(-5y^2+6y+2)= | | 7x-15(x-7)=9x | | 300x=1200 | | (3y-5)+(6y+20)=135+y | | 2+a/4-1 | | -5x+6=-x-2 | | 5x^2+5x+1=0 | | 34+2y-11=10y-13-2y | | (x+15)+(x-23)=44 | | p-18=15 | | 23x+x^2=12 | | 2x+3=-2 | | .2=.07+x(.12) | | x+3-14x+11=3x-12-10x | | x/22+3.2=16 | | 30x+18/x=-48 | | n+23= | | x/27=35 | | 36-9x=45 | | x-36=30 | | 6a+3a-5a-b= | | x+29=12 | | x-3x-6=-x | | 12a^3+39a^2-36a= |